A cholesteric liquid crystal smart window with a low operating voltage. (January 2022) - Oh, Seung-Won; Ji, Seong-Min; Han, Chan-Hee; Yoon, Tae-Hoon
Abstract: A dye-doped cholesteric liquid crystal smart window with a haze-free opaque state is demonstrated. We designed a random stripe pattern in the cholesteric phase, known as the fingerprint (FP) texture, as an initial state (opaque state). In the theoretical calculation of the LC alignment states, although the transmittance of the FP state is slightly higher than that of the twisted state (planar state), it is much lower than homogeneously aligned states. Moreover, we confirmed the proposed LC cell shows the lowest operating voltage (4 V) among guest-host liquid crystal cells because of vertical anchoring at the surfaces. Graphical abstract: Image 1 Highlights: A random stripe pattern (FP texture) in the cholesteric phase is used as the haze-free opaque state. The proposed LC cell shows low transmittance and the lowest operating voltage because of vertical anchoring at surfaces. We demonstrated the equation for the transmittance of fingerprint state and confirmed it with measured transmittance.